Exploratory Factor Analysis of Moral Disengagement Scale (MDS) in Indonesian Version - Purba, Andareas Kiser; Defi Syazana Nadhira; Devi Lusiria (In Trend : International Journal of Trends in Global Psychological Science and Education, 2025)
Adolescents are vulnerable to showing aggressive behavior that is often justified through the process of moral disengagement. This study aims to adapt and test the validity and reliability of the Indonesian version of the Moral Disengagement Scale (MDS) in adolescents aged 10–15 years. Participants in this study were 323 early adolescents selected through a purposive sampling method. Scale adaptation was carried out through the stages of forward-backward translation, expert judgment, Aiken-V test, and analysis using JASP version 19.3. The results of the validity test showed that 18 of the 19 items had an item-total correlation above 0.3, indicating good discrimination. The Cronbach's Alpha reliability value of 0.883 indicated high internal consistency. Exploratory factor analysis (EFA) showed a KMO value of 0.892 and Bartlett's Test was significant (p <0.01), so it was worthy of further analysis. The Indonesian version of the MDS scale forms three main factors that describe the dimensions of aggression justification, beliefs about the treatment of others, and moral rationalization. This finding is in line with the three-factor model developed by Rubio-Garay et al. (2017). The Indonesian version of the MDS scale has been proven valid and reliable, and is able to describe the tendency of moral disengagement in adolescents in the context of Indonesian culture.